2009
DOI: 10.1111/j.1469-7580.2009.01046.x
|View full text |Cite
|
Sign up to set email alerts
|

Origin and evolution of the integumentary skeleton in non‐tetrapod vertebrates

Abstract: Most non-tetrapod vertebrates develop mineralized extra-oral elements within the integument. Known collectively as the integumentary skeleton, these elements represent the structurally diverse skin-bound contribution to the dermal skeleton. In this review we begin by summarizing what is known about the histological diversity of the four main groups of integumentary skeletal tissues: hypermineralized (capping) tissues; dentine; plywood-like tissues; and bone. For most modern taxa, the integumentary skeleton has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
321
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(330 citation statements)
references
References 162 publications
(372 reference statements)
8
321
1
Order By: Relevance
“…15a). Ganoine, as in most actinopterygians, is composed of multiple layers (Sire et al, 2009), as can be seen in photographs under normal and polarized light (Fig. 15b and c).…”
Section: Micromorphology and Histologymentioning
confidence: 73%
See 1 more Smart Citation
“…15a). Ganoine, as in most actinopterygians, is composed of multiple layers (Sire et al, 2009), as can be seen in photographs under normal and polarized light (Fig. 15b and c).…”
Section: Micromorphology and Histologymentioning
confidence: 73%
“…1 from the La Cantera Formation are of the lepisosteoid type with multiple ganoine layers, canaliculi of Williamson (Schultze, 1966(Schultze, , 2015Sire et al, 2009) in the basal bony layer, and no dentine. The surface of the flank scales is smooth, and microscopically it is bare of tubercles or denticles.…”
Section: Comparison With Scales Of Other Teleosteomorpha and Other Nementioning
confidence: 99%
“…Sire, et al [46] note that the dermal plates in tetraodontiformes are composed of only bone. However, the order tetraodontiformes is so diverse in morphology that it is unlikely that every modified scale across the order is compositionally identical.…”
Section: Spinesmentioning
confidence: 99%
“…Giles et al (2013) demonstrated that this dermal architecture is also plesiomorphic with respect to placoderms, regardless of whether they are perceived as monophyletic or paraphyletic. Osteichthyans possess comparable dermal skeletal architecture, although their tubercles are capped with ganoine or enamel [ganoine is a hypermineralised tissue developmentally comparable to enamel (Sire et al, 1987;Sire, 1994;Sire et al, 2009)]. Chondrichthyans, the sister group to all other crown-gnathostomes, possess dermal denticles capped with enameloid, thus the phylogenetic distribution of dermal skeletal capping tissues suggests ganoine is apomorphic with respect to osteichthyans.…”
Section: The Pleisiomorphic Condition Of the Vertebrate Dermal Skeletonmentioning
confidence: 99%